Pyomelanin-Producing Brevundimonas vitisensis sp. nov., Isolated From Grape (Vitis vinifera L.) - Jiang, Lingmin; Jeon, Doeun; Kim, Jueun; Lee, Chul Won; Peng, Yuxin; Seo, Jiyoon; Lee, Ju Huck; Paik, Jin Hyub; Kim, Cha Young; Lee, Jiyoung (Frontiers in Microbiology, 2021)
A novel endophytic bacterial strain, designated GR-TSA-9T, was isolated from surface-sterilized grape (Vitis vinifera L.). 16S rRNA gene sequence analyses showed that the isolate was grouped within the genus Brevundimonas, displaying the highest similarity with Brevundimonas lenta DS-18T (97.9%) and Brevundimonas kwangchunensis KSL-102T (97.8%) and less than 97.5% similarity with other members of Brevundimonas. The strain GR-TSA-9T was a gram negative, rod shaped, facultatively anaerobic, catalase and oxidase positive, and motile bacterium. Its growth occurred at 10–37°C (optimally 25–30°C), at pH 7.0–8.0, and in NaCl 0–1% (optimally 0%). It contained ubiquinone-10 as a respiratory quinone, and the major cellular fatty acids (>10% of the total) were C16:0 (14.2%) and summed feature 8 (C18:1ω7c and/or C18:1ω6c, 65.6%). The polar lipids present in the strain were phosphoglycolipids, phosphatidylglycerol, 1,2-di-O-acyl-3-O-[d-glucopyranosyl-(1→4)-α-d-glucopyranuronosyl]glycerol, and unidentified lipids (L1, L2, and L4). The strain had one 2,976,716bp circular chromosome with a G+C content of 66.4%. The digital DNA–DNA hybridization value between strain GR-TSA-9T and B. lenta DS-18T was 20.9%, while the average nucleotide identity value was 76.7%. In addition, the dDDH and ANI values to other members in this genus, whose genome sequences are available, are less than 21.1 and 77.6%. Genome annotation predicted the presence of some gene clusters related to tyrosine degradation and pyomelanin formation. Strain GR-TSA-9T produced a brown melanin-like pigment in the presence of L-tyrosine-containing media. The highest pigment production (0.19g/L) was observed in tryptic soy broth with 1.0mg/ml L-tyrosine at 25°C for 6days of culture. Biophysical characterization by ultraviolet (UV)–visible spectroscopy, Fourier-transform infrared spectroscopy, and electrospray ionization mass spectrometry confirmed that the pigment was pyomelanin. Additionally, melanized GR-TSA-9T cells could protect the cells against UVC exposure. The phylogenetic, genomic, phenotypic, and chemotaxonomic features indicated that strain GR-TSA-9T represents a novel melanin-producing species of Brevundimonas. The type strain was GR-TSA-9T (KCTC 82386T=CGMCC 1.18820T).